Novel two-chain fatty acid-based lipids for development of vancomycin pH-responsive liposomes against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA). (26th November 2019) - Makhathini, Sifiso S.; Kalhapure, Rahul S.; Jadhav, Mahantesh; Waddad, Ayman Y.; Gannimani, Ramesh; Omolo, Calvin A.; Rambharose, Sanjeev; Mocktar, Chunderika; Govender, Thirumala
Abstract: The development of bacterial resistance against antibiotics is attributed to poor localisation of lethal antibiotic dose at the infection site. This study reports on the synthesis and use of novel two-chain fatty acid-based lipids (FAL) containing amino acid head groups in the formulation of pH-responsive liposomes for the targeted delivery of vancomycin (VAN). The formulated liposomes were characterised for their size, polydispersity index (PDI), surface charge and morphology. The drug-loading capacity, drug release, cell viability, and in vitro and in vivo efficacy of the formulations were investigated. A sustained VAN release profile was observed and in vitro antibacterial studies against S. aureus and MRSA showed superior and prolonged activity over 72 h at both pH 7.4 and 6.0. Enhanced antibacterial activity at pH 6.0 was observed for the DOAPA-VAN-Lipo and DLAPA-VAN-Lipo formulations. Flow cytometry studies indicated a high killing rate of MRSA cells using DOAPA-VN-Lipo (71.98%) and DLAPA-VN-Lipo (73.32%). In vivo studies showed reduced MRSA recovered from mice treated with formulations by four- and two-folds lower than bare VN treated mice, respectively. The targeted delivery of VAN can be improved by novel pH-responsive liposomes from the two-chain (FAL) designed in this study.